Evolution: how genes and their variation got here - Weiss, Kenneth (Henry Stewart Talks, 2007)
Evolution by phenotype, Basic factors of evolutionary change, Mutation, Genetic drift, Natural selection, Gene flow, Current human variation, Human global Y chromosome haplotype distribution, Human global mtDNA haplotype distribution, Selection for skin pigmentation and human evolution, Genetic variation and selection for resistance to various forms of malaria, Phenylketonuria (PKU), Deafness, Breast cancer